STRATEGI AKOMODASI KOMUNIKASI MAHASISWA PERANTAU DALAM MENGATASI HAMBATAN BAHASA DAN CULTURE SHOCK DI LINGKUNGAN KAMPUS - Meltri Fisrano; Maharani; Emah Ria; Andini Putri Melati; Sri Hertimi (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2026)
Being a student from other countries in a new environment is certainly not easy. This study aims to determine the communication accommodation strategies employed by students from other countries at the Faculty of Da'wah and Communication (FDK) at UIN Raden Fatah Palembang in dealing with language barriers and culture shock. Using Howard Giles' communication accommodation theory, this qualitative study collected data through in-depth interviews with 10 students from outside South Sumatra studying at FDK. The results showed that all informants experienced mild culture shock related to food, the assertive speech rate of the local community, and language differences (Palembang). To overcome these challenges, students from other countries tended to employ convergence strategies, striving to harmonize their speaking style and learn local vocabulary such as